A "user-friendly" phantom to conduct Quality Controls on MRgFUS device. Issue 1 (1st January 2022) - Acri, G; Caridi, F; Testagrossa, B; Gurgone, S; Anfuso, C; Paladini, G; Vermiglio, G; Greco, C; Venuti, V
Abstract: Magnetic Resonance guided Focused Ultrasound Surgery (MRgFUS) is a hybrid technique which uses Magnetic Resonance (MR) to obtain morphological information of the examined anatomical district and Focused Ultrasound Surgery (FUS) to ablate the body region under investigation by using MR as guidance. To ensure patients' safety is necessary to establish periodic Quality Controls (QCs) providing a complete evaluation of system status. QCs cannot be done directly on patients, for this reason, dedicated phantoms are used to guarantee the maintenance of quality over equipment lifetime. Several phantoms are available on the market, which are distributed by manufacturers and specific to the medical equipment, resulting in closed systems. In this study, we idealized, developed and created a prototype of a completely ";user-friendly"; phantom, to conduct QCs on FUS devices. It consists of an empty cylinder of polymethylmetacrylate (PMMA), that can be filled with different fluids and various inserts, available for the Medical Physicists, to perform test measurements on different parameters (size of FUS spot, precision of FUS spot, linearity of FUS power, linearity of electric power, evaluation of target temperature). The obtained results demonstrated that the novel phantom represents a useful and adaptable device that could be used during FUS QCs evaluations.